Psychological and psychopathological features of patients with hyperthyroidism in different clinical conditions - I. Ishchuk (Kazimierz Wielki University, 2018)
The article presented is devoted to the investigation and systematization of psychopathological disorders in the structure of psychoendocrine syndrome in patients with hyperthyroidism. The object: 100 patients with hyperthyroidism treated at the Ukrainian Scientific and Practical Center of endocrine surgery, endocrine transplantation of organs and tissues of the Ministry of Health of Ukraine. The consistent use of anamnestic, psychodiagnostic, clinical-psychopathological and statistical methods revealed a link between the states of compensation and decompensation of the hormonal status and the severity level of psychopathological components of psychoendocrine syndrome in hyperthyroidism.